SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-3607
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Pressure Effects in the Nondimensional Tire Model

Abstract: Inflation pressure affects every aspect of tire performance.Most tire models, including the Radt/Milliken Nondimensional Tire Model, are restricted to modeling a single inflation pressure at a time. This is a reasonable limitation, in that the Nondimensional model forms an input/output relationship between tire operating conditions and force & moment outputs. Traditional operating conditions are normal load, slip angle, inclination angle, slip ratio and road surface friction coefficient.Tire pressure is more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…和力矩都直接作用于轮胎上 [1] 。因此轮胎力学的研 究对车辆动力学来说至关重要。轮胎气压和载荷的 变化会改变其力学特性,进而影响车辆性能 [1][2][3] ,并 且,胎压是轮胎在使用中最易调节的参数 [4] ,载荷 又是随车辆行驶过程不断变化的参数,因此胎压和 载荷对轮胎力学特性的影响具有重要的研究意义。 近年来,在胎压和载荷对轮胎力学特性的影响 方面国内外学者从事了诸多研究。KASPRZAK 等 [4][5][6] 研究了胎压对轮胎力和力矩的影响,发现其影响主 要表现在刚度、摩擦因数、峰值回正力矩系数和峰 值形状;并利用低阶的响应面方法拟合这些特性与 胎压的关系,成功地将胎压作为输入变量引入 Radt/Milliken 量纲一轮胎模型。卢荡等 [7] 研究了胎 压对 UniTire 中侧向力和回正力矩参数的影响,采 用内插值的方法对胎压影响进行高精度预测。 HÖPPING 等 [8] 通过研究发现纵滑刚度随胎压的变 化主要是因为胎压变化改变了轮胎接地印迹长度,峰 值摩擦因数对应的纵向滑移率随胎压增大而增大的 原因是,接地印迹长度的减小导致了胎面单元平均 切应力的减小,此外还对峰值摩擦因数等特性进行 了研究并将胎压作为输入变量引入到魔术公式中。 阳超等 [9][10][11] 前期重点针对胎压和载荷的耦合因素对 轮胎力学特性的影响进行了深入研究,并建立了考 [12][13][14][15]…”
Section: 驱动、制动、转向等工况行驶时,地面对汽车的力unclassified
“…和力矩都直接作用于轮胎上 [1] 。因此轮胎力学的研 究对车辆动力学来说至关重要。轮胎气压和载荷的 变化会改变其力学特性,进而影响车辆性能 [1][2][3] ,并 且,胎压是轮胎在使用中最易调节的参数 [4] ,载荷 又是随车辆行驶过程不断变化的参数,因此胎压和 载荷对轮胎力学特性的影响具有重要的研究意义。 近年来,在胎压和载荷对轮胎力学特性的影响 方面国内外学者从事了诸多研究。KASPRZAK 等 [4][5][6] 研究了胎压对轮胎力和力矩的影响,发现其影响主 要表现在刚度、摩擦因数、峰值回正力矩系数和峰 值形状;并利用低阶的响应面方法拟合这些特性与 胎压的关系,成功地将胎压作为输入变量引入 Radt/Milliken 量纲一轮胎模型。卢荡等 [7] 研究了胎 压对 UniTire 中侧向力和回正力矩参数的影响,采 用内插值的方法对胎压影响进行高精度预测。 HÖPPING 等 [8] 通过研究发现纵滑刚度随胎压的变 化主要是因为胎压变化改变了轮胎接地印迹长度,峰 值摩擦因数对应的纵向滑移率随胎压增大而增大的 原因是,接地印迹长度的减小导致了胎面单元平均 切应力的减小,此外还对峰值摩擦因数等特性进行 了研究并将胎压作为输入变量引入到魔术公式中。 阳超等 [9][10][11] 前期重点针对胎压和载荷的耦合因素对 轮胎力学特性的影响进行了深入研究,并建立了考 [12][13][14][15]…”
Section: 驱动、制动、转向等工况行驶时,地面对汽车的力unclassified
“…The effect of tire inflation pressure on tire properties has also been studied in the case of smaller tires (for example, car or motorbike tires) than the ones used in typical airliners. Kasprzak, Lewis and Milliken 15,16 studied the effects of inflation pressure on tire properties to improve the accuracy and adaptability of the Radt/Milliken nondimensional tire model. 17 Similar experimental studies have been performed by Ramji, Goel and Saran 18 on small-sized pneumatic tires.…”
Section: Lateral Dampingmentioning
confidence: 99%
“…The vast majority of these have focused on automobile or racing car tyres. Kasprzak et al [1,2] described the influence of the tyre inflation pressure on the lateral force and aligning torque properties of a racing car tyre through measurements. The study showed that a lower inflation pressure could increase the lateral force capability of the tyre under normal loads, while the opposite effect was observed under higher loads.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that a higher inflation pressure yields a lower cornering stiffness under light normal loads but a higher cornering stiffness *Corresponding author: CONCAVE Research Centre, Department of Mechanical and Inustrial Engineering, Concordia University, Montreal, Quebec, Canada. email: mohdsolihat@yahoo.com; h_alsoli@encs.concordia.ca under higher vertical loads, as reported in references [1] and [2]. These effects were further incorporated into an analytical tyre model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation